Pengaruh Pembelajaran Konflik Kognitif Untuk Meningkatkan Kemampuan Berpikir Kreatif Matematis Siswa SMA - Ika Meika; Asep Sujana (Universitas Mathla'ul Anwar Banten, 2015)
This research is mixed method with concurrent embedded strategy that aims to find out: (1) How the ability of mathematical creative thinking of superior students and asor students ; (2) Iscreative thinking ability of students who learn by learning cognitive conflict better than the conventional learning based on students' pre requisites ability (superior andasor). The population of the research is SMAN CMBBS students, with two classses of class XI IPA as sample. The instruments used in this research are multiple choice mathematics test reasoned and description, teachers and students activity observation sheets, and interview about learning. The data are analyzed quantitatively and qualitatively that obtained from pre-test and post-test results and gain normalized. The results show that: (1) The creative thinking ability of superior students and asor students before learning is same; (2) The creative thinking ability of students who learn by learning cognitive conflict is better than the conventional learning based on students' pre requisites ability (superior).